Soil Fertility, Fertilizer, and the Maize Green Revolution in East Africa - Matsumoto, Tomoya; Yamano, Takashi (World Bank, Washington, DC, 2014)
This paper investigates the reasons for the low application of external fertilizers on farms in Kenya and Uganda. The analysis uses a large panel of household data with rich soil fertility data at the plot level. The authors control for maize seed selection and household effects by using a fixed-effects semi-parametric endogenous switching model. The results suggest that Kenyan maize farmers have applied inorganic fertilizer at the optimal level, corresponding to the high nitrogen-maize relative price, in one of the two survey years and also responded to the price change over time. In Uganda, even the low application of inorganic fertilizer is not profitable because of its high relative price. The authors conclude that policies that reduce the relative price of fertilizer could be effective in both countries, while the efficacy of policies based on improving farmers' knowledge about fertilizer use will be limited as long as the relative price of fertilizer remains high.